New equations for predicting the frost resistance of ceramic products by deformational parameters/Naujos keraminių gaminių atsparumo šalčiui prognozavimo lygtys naudojant deformacinius rodiklius - Kičaitė, Asta; Mačiulaitis, Romualdas (Journal of Civil Engineering and Management, 2001)
One of the important parameters describing durability is the resistance to frost. It can be determined by direct and rapid prediction methods. Investigations by direct methods last from some days to several months. Frost resistance of ceramic products can be estimated fast by rapid prediction methods. One of important directions of the rapid prediction methods is the dilatometric method, which is sensitive to the changes of internal structure and related to tensions and deformation by freezing and thawing. One of dilatometrie apparatus is DUM-01, which can establish many deformation parameters by one-sided freezing of ceramic bricks. Clay bricks made by plastic extrusion and by semi-dry pressing were tested. We have estimated what values of deformative parameters of ceramic bricks change in a wide range from negative to positive. The bigger the positive values of deformation parameters, the less number of ceramic samples is resistant to frost. We think that the observed negative values of deformation parameters appear because of water migration in ceramic bricks from defective zones. The ice formed in large pores does not destroy ceramic products and they have possibility to shrink. It was established that objective forecast for the frost resistance of ceramic bricks must be carried out using water absorption and two groups of deformation parameters. Prediction methods according to structural and deformational properties have been developed. Testing by these methods lasts 3 days. Rapid prediction methods for frost resistance of ceramics products are more convenient and prospective due to structural and deformational properties.Article in Lithuanian.First Published Online: 30 Jul 2012